CURRENT TRANSFER IN p-Si–n-(Si2)1-x(GaN)x HETEROSTRUCTURE - Zhuraev Asom Kuylibayevich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This paper presents the results of a study on the growth of substitutional solid solutions (Si2)1-x(GaN)x on single-crystal Si (111) substrates by liquid-phase epitaxy from a limited volume of a tin solution-melt in a hydrogen medium and the current-voltage characteristic (CVC) of p-Si-n-(Si2)1-x(GaN)x structures.